Actividad física e índice de masa corporal en personal administrativo de la Universidad Nacional de Loja - Rodríguez Pineda, María Luisa (2022)
The World Health Organization (WHO) defines physical activity as any movement produced by the skeleton muscles with the consequent energy consumption. The Body Mass Index (BMI) as a simple indicator of the relation between weight and height that can be used to determine nutritional status. The present research had the objective of determining the level of physical activity and BMI within the administrative staff of Universidad Nacional de Loja, this examination was performed according to gender and age group and the correlation between these two variables. The study was quantitative with transversal prospective cut, where the sample was of 141 participants, 45% men and 55% women who met the inclusion criteria, whose BMI was assessed and to determine the physical activity the International Physical Activity Questionnaire (IPAQ) was applied.67 % of the administrative staff showed nutritional alterations: 45% (n=62) presented overweight where the highlight was the feminine gender of ages between 41 to 64 years old with con 21% (n=29), 17% (n=24) displayed obesity type I the femenine gender predominated, mature adults 7% (n= 10), 2% (n=3) displayed obesity type II and III respectively, and ponderal insufficiency 1% (n=2) on both genders, 33% (n=47) presented normal weight predominating in the feminine gender in mature adults with 16% (n=22). Regarding the level of physical activity, 50% (n=77) shows a low level, where women of ages between 41 to 64 years old with 28% (n=39)stood out, 26 % (n=37) shows a high level, 24 % (n=34) presented moderate levels. When relating the variables of level of physical activity and BMI with the formula chi square, it was possible to demonstrate that there is a statistically significant relation and concluding that a low level of physical activity influences negatively in the BMI.